BANK CREDIT POLICY AND ECONOMIC GROWTH: A KEY FACTOR IN ENSURING FINANCIAL STABILITY - Muxammadiyev Kamoliddin G'ulomiddinovich; Tinchlikov Shoxjaxon Zafarjonovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Bank credit policy is a crucial determinant of economic growth and financial stability. This policy encompasses the strategies and measures implemented by central and commercial banks to regulate lending activities, interest rates, and credit conditions within an economy. By influencing the availability and cost of credit, bank credit policy directly affects investment, consumption, and overall economic activity. During periods of economic downturn, lower interest rates and easier credit conditions can stimulate borrowing and investment, while higher rates may restrain excessive borrowing in times of inflation. Effective credit policy also ensures financial inclusion, supporting underserved sectors and fostering entrepreneurship, particularly in small and medium-sized enterprises. However, unchecked credit expansion poses risks to financial stability, making it essential for regulators to balance growth with prudent risk management. Ultimately, well-designed bank credit policies contribute to longterm, sustainable growth by providing a stable financial environment and supporting emerging industries, thereby driving economic development and prosperity.